V for victory : a novel - Evans, Lissa (Harper, an imprint of HarperCollinsPublishers, 2021)
It's late 1944. In a large house next to Hampstead Heath, Vee Sedge is barely scraping by with a herd of lodgers to feed and her young charge Noel, almost fifteen now, to clothe and educate. When she witnesses an accident and finds herself in court, the repercussions are both unexpectedly marvelous and potentially disastrous. Because Vee is not actually the person she's pretending to be, and neither is Noel.